2021
DOI: 10.7759/cureus.14248
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Melanonychia as a Solitary Black Linear Vertical Nail Plate Streak: Case Report and Literature Review of Candida-Associated Longitudinal Melanonychia Striata

Abstract: Longitudinal melanonychia striata, presenting as a black linear vertical band of the nail plate, can be caused by pigmented lesions and non-pigmented etiologies. A fungal infection of the nail plate, also referred to as onychomycosis or tinea unguim, can result from dermatophytes, non-dermatophyte molds, and Candida . Albeit rare, Candida -associated fungal melanonychia can present as a longitudinal black nail plate streak. The case of a 79-year-old man who develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…[4]. In 2020, an article from Hak-Jun et al reported that multicolor pigmentation was present in 65% of cases [32].…”
Section: Discussionmentioning
confidence: 99%

Fungal Melanonychia: A Systematic Review

Rodríguez-Cerdeira,
Martínez-Herrera,
Cortés-López
et al. 2024
Microorganisms
“…[4]. In 2020, an article from Hak-Jun et al reported that multicolor pigmentation was present in 65% of cases [32].…”
Section: Discussionmentioning
confidence: 99%

Fungal Melanonychia: A Systematic Review

Rodríguez-Cerdeira,
Martínez-Herrera,
Cortés-López
et al. 2024
Microorganisms
“…Tinea may appear either early during the first two months following tattoos, or later in a healed tattoo [88]. The main dermatophytes isolated from tattoos included Trichophyton rubrum, Microsporum canis, Trichophyton tonsurans, Epidermophyton floccosum, and Microsporum gypseum [89].…”
Section: (Figure)mentioning
confidence: 99%
“…It has been identified as an opportunistic pathogen in patients with systemic disease or onycholysis. The nail plate discoloration caused by Candida parapsilosis can be diffusely green or black or a linear streak of black, green, white, or yellow [2,3].…”
Section: Introductionmentioning
confidence: 99%